2022
DOI: 10.1007/s41669-022-00344-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Resource Utilization and Cost of Patients with Multiple Myeloma in Germany: A Retrospective Claims Data Analysis

Abstract: Objective This study aimed to analyze the healthcare resource use (HCRU) and associated costs of multiple myeloma (MM) using German claims data. Methods Anonymized claims data from one of the largest sickness funds in Germany were analyzed. Costs and HCRU were calculated from the perspective of the statutory health insurance. To analyze MM-associated incremental costs in a most recent calendar period for an overall MM population (31 March 2018-31 March 2019), a prevalent cohort of MM patients (continuously ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…There is a scarcity in the literature of similar analyses including data from the last three years, during which, several regimens with meaningful clinical and economic impacts have been added to the MM therapeutic armamentarium. However, available studies describing MM treatment costs in earlier periods also showed progressive yearly increases [17,20], and multiple studies assessing MM healthcare resource utilization found that medicines were a key cost driver in any line of treatment [18,19,21,[47][48][49][50]. The mean cost per patient in a healthcare resource utilization study conducted in France was EUR 61,500 [22], almost EUR 10,000 lower than the figure reported here (EUR 70,816).…”
Section: Discussioncontrasting
confidence: 51%
“…There is a scarcity in the literature of similar analyses including data from the last three years, during which, several regimens with meaningful clinical and economic impacts have been added to the MM therapeutic armamentarium. However, available studies describing MM treatment costs in earlier periods also showed progressive yearly increases [17,20], and multiple studies assessing MM healthcare resource utilization found that medicines were a key cost driver in any line of treatment [18,19,21,[47][48][49][50]. The mean cost per patient in a healthcare resource utilization study conducted in France was EUR 61,500 [22], almost EUR 10,000 lower than the figure reported here (EUR 70,816).…”
Section: Discussioncontrasting
confidence: 51%
“…These guidelines predominantly advocate for proteasome inhibitor-based therapies, as they offer superior response rates and improved survival outcomes, alongside the use of thalidomide, melphalan, lenalidomide, and cyclophosphamide [14]. In comparison to cost estimates from other countries, the monthly cost per patient for therapy medications alone in Singapore is higher than those reported in China [15], The Netherlands [16], and Germany [17], but considerably lower than the costs in the United States [18,19], which are nearly double. Several factors contribute to these variations.…”
Section: Discussionmentioning
confidence: 99%
“…All of these aspects are the primary contributors to the socioeconomic burden of the disease (Ernst & Young, 2018). According to recent studies, MM is a disease that poses a large burden on the healthcare system, in terms of therapy costs and healthcare resource consumption (Ashcroft et al, 2018; Kocaata et al, 2022; Kolovos et al, 2019; Ouchveridze et al, 2022), and to the patient and society given its financial toxicity (labour productivity losses, informal care and out‐of‐pocket expenses) (Jackson et al, 2019; Ortega‐Ortega et al, 2018; Ouchveridze et al, 2022; Parker et al, 2022). Therefore, the improvement in the management of the symptoms associated with MM, as well as the greater control of the disease, will benefit the quality of life of the patients in addition to a more efficient use of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%